2018
DOI: 10.31661/jbpe.v0i0.771
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Validity of a Nonlinear J-Shaped Dose-Response Relationship in Cancers Induced by Exposure to Radiofrequency Electromagnetic Fields

Abstract: The radiofrequency electromagnetic fields (RF-EMFs) produced by widely used mobile phones are classified as possibly carcinogenic to humans by International Agency for Research on Cancer (IARC). Current data on the relationship between exposure to RF-EMFs generated by commercial mobile phones and brain cancer are controversial. Our studies show that this controversy may be caused by several parameters. However, it seems that the magnitude of exposure to RF-EMFs plays a basic role in RF-induced carcinogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…The third scientist was another epidemiologist from Massey University, one of whose many research projects involves participation in the multinational INTEROCC project, an offshoot of the controversial INTERPHONE project. He reports to the committee that INTEROCC has not found any effect of occupational RF exposure on meningiomas and is winding down; according to the meeting notes, he fails to make any mention of the methodological controversy generated by this negative finding [16][17][18][19]. No laboratory scientist-no physiologist, neuroscientist, biochemist or biophysicist, whose professional expertise might have enabled them to discuss the many scientific publications now available on the specific mechanisms by which RF affects biological organisms-was present.…”
mentioning
confidence: 99%
“…The third scientist was another epidemiologist from Massey University, one of whose many research projects involves participation in the multinational INTEROCC project, an offshoot of the controversial INTERPHONE project. He reports to the committee that INTEROCC has not found any effect of occupational RF exposure on meningiomas and is winding down; according to the meeting notes, he fails to make any mention of the methodological controversy generated by this negative finding [16][17][18][19]. No laboratory scientist-no physiologist, neuroscientist, biochemist or biophysicist, whose professional expertise might have enabled them to discuss the many scientific publications now available on the specific mechanisms by which RF affects biological organisms-was present.…”
mentioning
confidence: 99%
“…people who use their mobile phones occasionally). New studies support our previously proposed J-shaped dose-response relationship and show even hormetic effects at low levels while at high levels an irreversible damage and hence increased risk of cancer would be possible [8]. To investigate whether RF-EMFs are genotoxic, Sun et al compared the effects of 1,800 MHz RF-EMF exposure on genomic DNA in mouse embryonic fibroblasts (MEFs) with proficient (Atm+/+) or deficient (Atm−/−) ATM.…”
supporting
confidence: 61%
“…Belyaev reported in 2017 that a proper metrics for exposure to RF fields is a combination of exposure duration and power flux density of the field [5]. Evidence supporting a nonlinear dose-response relationship continued to gather, and recently in 2019 the authors of [6] demonstrated that a nonlinear J-shaped dose-response relationship exists in carcinogenesis due to mobile phone radiation.…”
Section: Introductionmentioning
confidence: 99%